Virological failure and treatment switch after ART initiation among people living with HIV with and without routine viral load monitoring in Asia. Issue 8 (26th August 2022) - Teeraananchai, Sirinya; Law, Matthew; Boettiger, David; Mata, Nicole De La; Gupte, Nikhil; Chan, Yun‐ting Lawrence; Pham, Thach Ngoc; Chaiwarith, Romanee; Ly, Penh Sun; Chan, Yu‐Jiun; Kiertiburanakul, Sasisopin; Khusuwan, Suwimon; et al.
Abstract: Introduction: Viral load (VL) testing is still challenging to monitor treatment responses of antiretroviral therapy (ART) for HIV treatment programme in Asia. We assessed the association between routine VL testing and virological failure (VF) and determine factors associated with switching to second‐line regimen. Methods: Among 21 sites from the TREAT Asia HIV Observational Database (TAHOD), people living with HIV (PLHIV) aged ≥18 years initiating ART from 2003 to 2021 were included. We calculated the average number of VL tests per patient per year between the date of ART initiation and the most recent visit. If the median average number of VL tests was ≥ 0.80 per patient per year, the site was classified as a routine VL site. A site with a median < 0.80 was classified into the non‐routine VL sites. VF was defined as VL ≥1000 copies/ml during first‐line therapy. Factors associated with VF were analysed using generalized estimating equations with Poisson distribution. Results: Of 6277 PLHIV starting ART after 2003, 3030 (48%) were from 11 routine VL testing sites and 3247 (52%) were from 10 non‐routine VL testing sites. The median follow‐up was 9 years (IQR 5–13). The median age was 35 (30–42) years; 68% were male and 5729 (91%) started non‐nucleoside reverse‐transcriptase inhibitor‐based regimen. The median pre‐ART CD4 count in PLHIV from routine VL sites was lower compared to non‐routine VL sites (144 vs. 156 cells/mm 3, p <0.001). Overall, 1021 subsequent VF at a rate of 2.15 (95% CI 2.02–2.29) per 100 person‐years (PY). VF was more frequent at non‐routine VL sites (adjusted incidence rate ratio 2.85 [95% CI 2.27–3.59]) compared to routine VL sites. Other factors associated with an increased rate of VF were age <50 years and CD4 count <350 cells/mm 3 . A total of 817 (13%) patients switched to second‐line regimen at a rate of 1.44 (95% CI 1.35–1.54) per 100 PY. PLHIV at routine VL monitoring sites were at higher risk of switching than those at non‐routine VL sites (adjusted sub‐hazard ratio 1.78 95% CI [1.17–2.71]). Conclusions: PLHIV from non‐routine VL sites had a higher incidence of persistent VF and a low switching regimen rate, reflecting possible under‐utilized VL testing.